2015
DOI: 10.1007/s13205-015-0278-5
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment for suppression of acrylamide formation in fried potato chips using L-asparaginase from Bacillus subtilis

Abstract: It has been reported that acrylamide, a potential carcinogen, is formed from the reaction of L-asparagine (L-Asn) and reducing sugars contained in foods during heating processes and free asparagine is a limiting factor for acrylamide formation. It has been reported that potato products such as potato chips, which are made through heating processes, contain high levels of acrylamide. To decrease the amount of L-Asn in potatoes using L-asparaginase, effective treatment conditions of sliced potatoes with the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, Elmore et al (2015) have reported no significant differences between acrylamide contents of pre-stored and stored potato varieties during 2 and 6 months. Moreover, it was notified that acrylamide formation could be significantly limited when providing high reduction in asparagine content (Dias & Sato, 2016;Onishi et al, 2015;Pedreschi, Kaack, & Granby, 2008;Zuo, Zhang, Jiang, & Mu, 2015). Halford et al (2012) have emphasized that low acrylamide content could be provided in potato varieties having low precursors content regardless of heat process.…”
Section: Introductionmentioning
confidence: 99%
“…However, Elmore et al (2015) have reported no significant differences between acrylamide contents of pre-stored and stored potato varieties during 2 and 6 months. Moreover, it was notified that acrylamide formation could be significantly limited when providing high reduction in asparagine content (Dias & Sato, 2016;Onishi et al, 2015;Pedreschi, Kaack, & Granby, 2008;Zuo, Zhang, Jiang, & Mu, 2015). Halford et al (2012) have emphasized that low acrylamide content could be provided in potato varieties having low precursors content regardless of heat process.…”
Section: Introductionmentioning
confidence: 99%
“…Asparaginase from food-grade Bacillus subtilis was applied to potato chips (Onishi, Prihanto, Yano, Takagi, Umekawa, & Wakayama, 2015). Compared to a control sample, 40 U of asparaginase led to 80% reduction in acrylamide.…”
Section: New Sources Of Asparaginasementioning
confidence: 99%
“…The conditions of the industrial scale activities are related to the maintenance of its activity in environments with temperature variation (55°C to 121°C and -2°C to 20°C), pressure (> 500 atmospheres), alkalinity or acidity pH (pH> 8, pH <4), salinity Besides this, the food industry has been showing increasing attention by L-asparaginase as a promising agent for acrylamide mitigation, considering that the thermal treatment of foods rich in carbohydrates mainly the amino acid asparagine culminates in several chemical reactions, among them the Maillard Reaction (PEDRESCHI et al, 2006;HENDRIKSEN et al, 2013). Various microorganisms of L-asparaginase producers have been described as potential candidates for use in foods as a mitigation of acrylamide formation since up to 99% reduction in the formation of acrylamide in cold potatoes was obtained using the enzyme from microbial sources (ONISHI et al, 2015).…”
Section: Introductionmentioning
confidence: 99%